Penerapan Self Service Technology ATM terhadap Kepuasan Pelanggan (Studi di Bank Mandiri Semarang) - Yohan Wismantoro (MEDIA, 2013)
Information technology can be seen in all aspects of life, both in business activities and in social life. This study aims to determine the ease of use factor, convenience and performance together against the perceived satisfaction of bank customers. Population in this research are the customers Bank Mandiri Semarang with convenience sampling methods of 100 responden. Analysis tools used in this study is regression analysis. The research proves that ease of use, convenience variables, and performance positively proven and significant effect on satisfaction